2001
DOI: 10.1016/s0896-6273(01)00533-5
|View full text |Cite
|
Sign up to set email alerts
|

Reward Circuitry Activation by Noxious Thermal Stimuli

Abstract: Using functional magnetic resonance imaging (fMRI), we observed that noxious thermal stimuli (46 degrees C) produce significant signal change in putative reward circuitry as well as in classic pain circuitry. Increases in signal were observed in the sublenticular extended amygdala of the basal forebrain (SLEA) and the ventral tegmentum/periaqueductal gray (VT/PAG), while foci of increased signal and decreased signal were observed in the ventral striatum and nucleus accumbens (NAc). Early and late phases were o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

34
372
5
1

Year Published

2006
2006
2011
2011

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 450 publications
(412 citation statements)
references
References 107 publications
34
372
5
1
Order By: Relevance
“…Coghill and colleagues demonstrated with PET that pain is a distributed bilateral process, while for non-noxious heat stimulation, only contralateral activation is observed (Coghill et al 1999). In addition, other investigators have found temporal differences for noxious and non-noxious cortical responses (Becerra et al 2001;Chen et al 2006). These studies seem to indicate that the temporal response to noxious stimuli in S1 is distinct from innocuous stimuli; pain seems to produce a prolonged or biphasic response usually extending beyond the duration of the stimulus whereas innocuous stimuli produce a response similar to other evoked hemodynamic responses.…”
Section: Introductionmentioning
confidence: 93%
See 4 more Smart Citations
“…Coghill and colleagues demonstrated with PET that pain is a distributed bilateral process, while for non-noxious heat stimulation, only contralateral activation is observed (Coghill et al 1999). In addition, other investigators have found temporal differences for noxious and non-noxious cortical responses (Becerra et al 2001;Chen et al 2006). These studies seem to indicate that the temporal response to noxious stimuli in S1 is distinct from innocuous stimuli; pain seems to produce a prolonged or biphasic response usually extending beyond the duration of the stimulus whereas innocuous stimuli produce a response similar to other evoked hemodynamic responses.…”
Section: Introductionmentioning
confidence: 93%
“…A 3×3 cm 2 thermode (TSA-2001, Medoc Inc., Haifa, Israel) was used to deliver the painful 46 °C thermal stimuli. This equipment has been utilized in other fMRI pain experiments (Becerra et al 2001). The thermal probe was lowered down onto the hand of the subject upon prompting and removed at the end of each stimulus.…”
Section: Paradigmmentioning
confidence: 99%
See 3 more Smart Citations